Fungsi Sosial Legenda Watu Dodol dalam Tradisi Puter Kayun Bagi Masyarakat Banyuwangi - Nur Hanifiyah Salsabila; Eggy Fajar Andalas (Jurnal Bahasa dan Sastra, 2022)
The legend of Watu Dodol which is still maintained to this day because it is considered a story that really happened by the people of Banyuwangi so that it gave rise to the traditions of the legend of the origin of Watu Dodol among the people of Boyolangu and surrounding areas. This research aims to describe the social function of the legend of Watu Dodol in the tradition of Puter Kayun and describe the stone that is the place where the tradition of puter kayun is carried out. This research uses the phenomenological approach used to reveal the phenomenon of the formation of watu dodol that has been experienced by the boyolangu community and its surroundings. Data collection is done with observation techniques, interviews, and document analysis. The results showed that the legend of Watu Dodol had an impact on the traditions preserved to date by the local community. This is related to the social function obtained by the community from traditions that are carried out routinely once a year in the month of Shawwal. The social function of watu dodol legend in the tradition of puter Kayun is among others as a means of entertainment, a means of education, strengthening social solidarity between communities, and as a group identity.